Educational and social insights from the biography of Lady Fatima Al-Zahra - Hamzh, Ali Falasteen (Thi Qar Arts Journal, 2024)
Abstract The follower of the biography of Mrs. Fatima Al-Zahra, peace be upon her, finds that she was the greatest woman in existence, whom the Holy Prophet Muhammad, may God’s prayers and peace be upon him and his family, described as the mother of her father, and he said about her that she was his soul between his two sides, and she was full of knowledge from her childhood to her martyrdom, peace be upon her. When Mrs. Zahra entered upon him, the Prophet used to take the initiative to stand up, and this indicates the greatness of this lady. He mentioned that when the Prophet returned from the battles, the first thing he did was pray in the mosque and then praise Mrs. Zahraa, peace be upon her .